Two new cavernicolous Ephippiochthonius species from Caucasian caves in Georgia (Arachnida: Pseudoscorpiones) - Gogshelidze, Mariam; Novák, János (Zootaxa, 2026)
Two new cavernicolous pseudoscorpion species, Ephippiochthonius boritiensis sp. nov. from Kozmani Cave, and Ephippiochthonius trapezoides sp. nov. from Tsintskila Cave in Georgia (Caucasus) are described and illustrated. Furthermore, a key for all epigean and cavernicolous Ephippiochthonius species in Georgia is also provided.